Outcomes of Teenage Pregnancy in Patients Presenting at Ayub Teaching Hospital Abbottabad - Khan, Sundas; Sarwar, Iram; Sameeh, Alina; Ayaz, Haiqa (Indus Journal of Bioscience Research, 2025)
Background: Teenage pregnancy is a major public health issue and it is associated with poor maternal and neonatal outcomes, especially in low resource settings where antenatal care is limited. Objective: To determine the frequency of outcomes of teenage pregnancy in patients presenting at a tertiary care hospital. Study Design: Prospective Cohort study. Duration and Place of Study: This study was conducted from 19th March 2025 to 19th June 2025 at Department of Obstetrics and Gynaecology, Ayub Teaching Hospital Abbottabad. Methodology: Total 98 teenage pregnant patients aged 13–19 years were included. Patients with singleton pregnancy and gestational age >24 weeks were selected, while those with medical disorders and fetal anomalies were excluded. Outcomes including anaemia, preterm delivery, low birth weight, low Apgar score and caesarean delivery were assessed. Data was analysed using IBM Statistical Package for Social Sciences version 26. Results: Mean age was 15.74 ± 1.80 years. Anaemia was most common outcome seen in 74 (75.50%) patients, followed by preterm delivery 64 (65.30%), low birth weight 54 (55.10%), low Apgar score 39 (39.80%) and caesarean delivery 27 (27.60%). Low birth weight showed significant association with age (p